Answer:
The answer is A
Step-by-step explanation:
Answer:
(x,y) => (x+3, y+4)
Step-by-step explanation:
Given a triangle DEF, D(4,2), E(3,3), F(2,1).
Centroid of the area (and the vertices) equals the mean of the coordinates, namely ( (4+3+2)/3, (2+3+1)/3 ) = (3,2)
To translate (3,2) to (6,6), we need the rule
(x,y) => x+(6-3), y+(6-2), or
(x,y) => (x+3, y+4)
After five weeks they will have the same amount of money.
<h2><u><em>
If you rather have the link to get this info lmk!!</em></u></h2>
Example: f(x) = 2x+3 and g(x) = x2
"x" is just a placeholder. To avoid confusion let's just call it "input":
f(input) = 2(input)+3
g(input) = (input)2
Let's start:
(g º f)(x) = g(f(x))
First we apply f, then apply g to that result:
Function Composition
- (g º f)(x) = (2x+3)2
What if we reverse the order of f and g?
(f º g)(x) = f(g(x))
First we apply g, then apply f to that result:
Function Composition
- (f º g)(x) = 2x2+3
We get a different result! When we reverse the order the result is rarely the same. So be careful which function comes first.
<h2 />